Optimalisasi Destinasi Wisata Alam Dan Digitalisasi Umkm Melalui Program Kuliah Kerja Nyata Di Desa Cilengkrang Sumedang - Muhammad Fadillah Aldiansyah; Nabila Putri Iskandar; Nurwulan Fitriani; Septy Amalia; Adang Sudrazat (CV. SINAR HOWUHOWU, 2026)
Cilengkrang Village in Sumedang Regency boasts natural tourism attractions such as Cakrabuana Waterfall and a local UMKM product, Jamparing Coffee. However, its development has been hindered by a lack of appealing facilities, insufficient signage, and traditional marketing strategies. This community service program, conducted through the Student Community Service (KKN) initiative, aims to maximize natural tourism potential and expand market reach for the local MSME by leveraging digital technology. A descriptive-qualitative methodology was employed, encompassing stages such as observation, interviews, partnership collaboration, field implementation, and outcome evaluation. The findings indicate that: (1) an aesthetic, nature-themed photo spot was established at Cakrabuana Waterfall to create an